Exploring the Social-Ecological System Connectivity of a Small-Scale Coral Reef Fisheries: The Case of Ranobe Bay, Madagascar - John Ricardo Hajandrainy Jeremiah; Jacqueline Razanoelisoa; Nurul Auliyah; Zairion; Luky Adrianto (Jurnal Pengelolaan Perikanan Tropis (Journal of Tropical Fisheries Management), 2025)
The southwest coast of Madagascar is home to small-scale Coral Reef Fisheries (CRFs), a vital activity for livelihoods and the local economy of the fishermen community. Understanding all about the components of this CRFs, the nature of their interactions and the resulting outcomes is crucial for designing policies that promote equitable and sustainable fisheries. This research aims to apply the Social-Ecological Systems (SES) framework and network analysis to assess the SES structure and the characteristics of Ranobe Bay CRFs, Madagascar. This research was carried out from September to October 2024, requiring primary data from field observations, interviews with respondents, and secondary data from literature studies. The Socio-Ecological Network Analysis (SENA) was used to analyze the connectivity of the CRFs in this region. The research findings of the SENA results showed that this fishery is heavily centered around the fishermen's community: the Masikoro and the Vezo as the main actors of this activity. Nevertheless, according to the cluster value analysis, the findings highlight a high number of clusters showcasing a low connectivity and less compact SES structure. Ranobe Bay's CRFs' sustainability depends on fishermen's central connectivity within the network, which can be strengthened through improved policies and management to ensure effective governance.